2015
DOI: 10.3402/gha.v8.29019
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and its effect on tuberculosis treatment outcomes in Ethiopia

Abstract: BackgroundPsychological distress is the major comorbidity among tuberculosis (TB) patients. However, its magnitude, associated factors, and effect on treatment outcome have not been adequately studied in low-income countries.ObjectiveThis study aimed to determine the magnitude of psychological distress and its effect on treatment outcome among TB patients on treatment.DesignA follow-up study was conducted in Addis Ababa, Ethiopia, from May to December 2014. Patients (N=330) diagnosed with all types of TB who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
93
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(118 citation statements)
references
References 31 publications
(62 reference statements)
16
93
2
1
Order By: Relevance
“…Most of the patients in this study were males older than 60 years, with lower incomes and education, and unemployed. These patient characteristics are similar to those reported in previous international articles (Beck et al., ; Tola et al., ; Virenfeldt et al., ; Wang et al., ; WHO, , Wu et al., ; Xiao, Zhou, Jiang, Zhao, & Xu, ), with the exception that patients in Kibrisli et al. 's () and Nikbakht et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most of the patients in this study were males older than 60 years, with lower incomes and education, and unemployed. These patient characteristics are similar to those reported in previous international articles (Beck et al., ; Tola et al., ; Virenfeldt et al., ; Wang et al., ; WHO, , Wu et al., ; Xiao, Zhou, Jiang, Zhao, & Xu, ), with the exception that patients in Kibrisli et al. 's () and Nikbakht et al.…”
Section: Discussionsupporting
confidence: 88%
“…() and Tola et al. (), who found a 44%–67.6% rate of depression among patients, of whom 65.2% were over 35 years old. The current study also showed no significant statistical correlation between demographic characteristics (gender, age, income, education, comorbidities) and depression, which is different from the results reported by Issa, Yussuf, and Kuranga () and Peltzer et al.…”
Section: Discussionmentioning
confidence: 94%
“…All analyses accounted for clustering by health facility using surveylogistic options of SAS Version 9.3. Based on previous literature, adjusted analyses controlled a priori for age, sex, relationship status, and time since HIV diagnosis (31, 32). Because internalized stigma was highly correlated with anticipated (rho = 0.422, p<0.0001) and enacted stigma (rho = 0.196; p < 0.0001), multivariable regression models were run separately to examine the relationship between each type of HIV-related stigma and psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic conditions may cause stress as a consequence of their symptoms, longterm prognosis, and other related issues such as treatment and its costs. Among people with chronic conditions, such as asthma, arthritis or diabetes, stress can intensify the effect of illness by increasing pain, functional limitations, and disability and decreasing adherence to medical treatment protocols, all of which may lead to psychological distress (i.e., a state of emotional suffering characterized by symptoms of depression and anxiety (10)), poorer health outcomes as well as increased risks of severe and chronic psychiatric and somatic complications (11)(12)(13). Moreover, perceived stress contributes significantly to higher mortality rates in a dose-response pattern (14), with even more stress-associated deaths evident among people with multimorbidity (15).…”
mentioning
confidence: 99%